2017
DOI: 10.1002/pc.24706
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, electrical, and thermal analysis of sisal fibril/kenaf fiber hybrid polyester composites

Abstract: A novel hybrid composition of sisal fibrils and kenaf fibers has been introduced first time as reinforcement in composite preparation for the environmental friendly high strength electrical insulation applications. Hybrid reinforcement was increased from 10 to 40 wt% in unsaturated polyester resin. The sisal fibril used in this study was extracted from sisal fiber. Alkali treatment was employed and FTIR analysis was done to study its effect on sisal fibrils and kenaf fibers. A positive hybridization effect was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 39 publications
(75 reference statements)
1
28
0
Order By: Relevance
“…Currently, nonwoven composites reinforced with cellulosic fibers have been used in the nonstructural applications in automotive industries . In spite of these advantages, the main challenges of using natural fibers include incompatibility with thermoplastic matrix, relatively low strength, batch‐to‐batch variability, and high moisture sensitivity . Therefore, it is necessary to remedy the shortcomings through chemical treatments to modify the fiber structure in order to achieve the exemplary mechanical properties as well as reduce the moisture uptake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, nonwoven composites reinforced with cellulosic fibers have been used in the nonstructural applications in automotive industries . In spite of these advantages, the main challenges of using natural fibers include incompatibility with thermoplastic matrix, relatively low strength, batch‐to‐batch variability, and high moisture sensitivity . Therefore, it is necessary to remedy the shortcomings through chemical treatments to modify the fiber structure in order to achieve the exemplary mechanical properties as well as reduce the moisture uptake.…”
Section: Introductionmentioning
confidence: 99%
“…[11] In spite of these advantages, the main challenges of using natural fibers include incompatibility with thermoplastic matrix, relatively low strength, batch-to-batch variability, and high moisture sensitivity. [12][13][14][15] Therefore, it is necessary to remedy the shortcomings through chemical treatments to modify the fiber structure in order to achieve the exemplary mechanical properties as well as reduce the moisture uptake. However, hybridization is considered as another efficient method to improve the mechanical strength and reduce moisture sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…[24,[26][27][28][29][30][31] From the available literature, it was also found that there are some research works related to 5 wt% of NaOH treatment. [32][33][34][35][36] Thus, 5 wt% concentration of NaOH solution was used in the present study. Prior to treatment, the TPS's were kept at 80 C for 8 h in the hot-air oven to remove moisture content.…”
Section: Alkali Treatment Of Tps'smentioning
confidence: 99%
“…Achieving a fiber/matrix adhesion, the natural fibers are usually exposed to a chemical treatment to increase the fiber contact region with a polymer. Alkali, silane, acetylation, and benzoylation can be mentioned as chemical reagents most used to treat the surface of the natural fibers [6][7]. This increase in adhesion occurs due to the modification of the fiber structure and chemical composition.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in adhesion occurs due to the modification of the fiber structure and chemical composition. As a result, the hydrophilic nature of fiber is reduced, and its compatibility with the matrix increases once the surface roughness of the fiber also increases [5][6][7]. A wide variety of products to produce polymeric composites is commercially available, and the polyester resin is applied as the main material [9][10].…”
Section: Introductionmentioning
confidence: 99%